I verbi di servizio (modali, aspettuali e causativi) e i verbi supporto nelle grammatiche descrittive d’italiano dal 1953 al 2005 - Godzich, Anna (Studia Romanica Posnaniensia, 2020)
The paper deals with Italian helping verbs (modal, aspectual, causative verbs) and light verbs which form complex predicates and with the rules that guide its use in Italian descriptive grammars published in Italy between 1953 and 2005. The author shows that those forms in both – traditional and contemporary Italian descriptive grammars are treated at the level of word classes whereas it could be more appropriate to discuss them as clause elements as they form complex predicates. In our opinion this way of describing such verbs is due to the tradition in Italy to focus on a form and not on function of an element. What is more, Italian grammarians tend to omit in Italian descriptive grammars noun predication and the role of semantic predicate (n pred.). The goal of the paper is to present the advantages of an integrated approach to helping verbs (modal, aspectual, causative verbs) and light verbs in modern Italian. The author emphasizes its importance for contemporary Italian FL syntax teaching.